Novel gene similar to nitrite reductase (NO forming) plays potentially important role in the latency of tuberculosis - Agrawal, Sonia; Gample, Suwarna; Yeware, Amar; Sarkar, Dhiman (Scientific Reports, 2021)
The development of the latent phenotype of Mycobacterium tuberculosis (Mtb) in the human lungs is the major hurdle to eradicate Tuberculosis. We recently reported that exposure to nitrite (10 mM) for six days under in vitro aerobic conditions completely transforms the bacilli into a viable but non-cultivable phenotype. Herein, we show that nitrite (beyond 5 mM) treated Mtb produces nitric oxide (NO) within the cell in a dose-dependent manner. Our search for the conserved sequence of NO synthesizing enzyme in the bacterial system identified MRA2164 and MRA0854 genes, of which the former was found to be significantly up regulated after nitrite exposure. In addition, the purified recombinant MRA2164 protein shows significant nitrite dependent NO synthesizing activity. The knockdown of the MRA2164 gene at mRNA level expression resulted in a significantly reduced NO level compared to the wild type bacilli with a simultaneous return of its replicative capability. Therefore, this study first time reports that nitrite induces dormancy in Mtb cells through induced expression of the MRA2164 gene and productions of NO as a mechanism for maintaining non-replicative stage in Mtb. This observation could help to control the Tuberculosis disease, especially the latent phenotype of the bacilli.